Prevalence & correlates of chronic perinatal pain – a study from India. (3rd April 2019) - Desai, Geetha; Sunil Kumar, G.; Manoj, L.; Gokul, G. R.; Beena, K. V.; Thennarasu, K.; Jaisoorya, T. S.
Abstract: Objectives: To study the prevalence of chronic perinatal pain among mothers who had infants between the ages of 13–25 months in the State of Kerala, India and to report its correlates in the socio-demographic, obstetric and psychological domains. Methods: A total of 9305 mothers selected by cluster random sampling were assessed cross-sectionally for chronic perinatal pain using a questionnaire by Junior Public Health Nurses (JPHNs). In addition, information regarding socio-demographic profile, obstetric history, infant details and perinatal depression were collected. Results: Of the 8302 (89.3%) valid responses, 552 (6.6%) mothers reported chronic perinatal pain. Among those with pain, 142 (25.6%) reported pain during pregnancy, 314 (56.7%) during postpartum and 96 (17.7%) during both periods. The commonest sites of pain reported were back 280 (51%) and pelvic region 110 (19%). Mothers with chronic perinatal pain were more likely to be younger, less educated, employed and from an urban background. Chronic perinatal pain was associated with obstetric complications, delivery by instrumental/caesarean section, non-exclusive breast feeding and higher maternal depression scores. Conclusion: Chronic pain is common among mothers in India during the perinatal period and greater attention needs to be given for it to be recognised and treated early.